Feasibility Analysis of Contents of Module Impulse and Momentum to Improve Student Math Skills Verbal Representation of Figures (R-VMGG) - I ketut Mahardika; I Wayan Sugiartana; Aris Doyan (Journal of Science and Science Education, 2021)
This article reports on the results of the development of impulse and momentum modules to improve the Verbal, Mathematical, Image and Graphic Representation (R-VMGG) abilities of high school students in Besuki Raya. The research objective was to describe the feasibility level of the content, the impulse module and momentum of the development results. The trials were carried out on small samples and large samples, after validation by experts. The large sample trial is carried out after completing the small sample trial which is carried out in stages from all learning activities with the impulse and momentum module. Trials with small samples and large samples were carried out to investigate the impulse and momentum module drafts of the development results in improving the R-VMGG abilities of SMAN students in Besuki Raya. Respondents in the small sample trial were 30 high school students, while the respondents in the large sample trial were 150 high school students. The results showed that the feasibility level of the contents of the developed modules reached a high category